Immune thrombocytopenia: literature review - S. G. Zakharov (Онкогематология, 2024)
Immune thrombocytopenia (ITP) is an autoimmune disease characterized by a decrease in platelet count, which often leads to bleeding. Evidence suggests that low platelet counts in ITP are the result of multiple factors, including impaired thrombocytopoiesis and changes in the immune response leading to platelet destruction. ITP is a heterogeneous disease with a course that is difficult to predict. In a significant number of cases, ITP becomes chronic, requiring long-term maintenance treatment, which leads to an increased risk of hemorrhagic complications and a decrease in quality of life. A deeper understanding ofthe etiology and pathogenesis ofthis disease makesit possible to identify potentialtherapeutic targets for the development of new effective treatments. This review summarizes recent advances in understanding the ITP pathophysiology, evaluating current therapeutic strategies and methods for predicting therapy response.